Kegiatan Penyuluhan Fisioterapi Mengenai Low Back Pain Pada Ibu Hamil dengan metode Massage dan Stretching di Kelurahan Merjosari Malang - Dina Azizah Wulandari; Rakhmad Rosadi; Lina Sriyatun (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2024)
Changes in the musculoskeletal system during the third trismester of pregnancy cause changes in body weight, abdominal muscle elasticity, and center of gravity which affect the balance of pregnant women. Back pain in pregnancy can be detrimental to the quality of life of pregnant women and is caused by changes in posture, hyperlordosis, paraspinal muscle tension, and decreased blood flow to the spine. Physiotherapy is a non-pharmacological solution by applying massage and stretching techniques. Massage helps relax muscles, reduce pain, increase blood flow, and improve muscle flexibility. Stretching plays a role in reducing pain, increasing flexibility, muscle strength, and preventing deformity. This activity is carried out by conveying physiotherapy information through leaflets as a promotional medium, pre-test, post-test, and questions to pregnant women to measure knowledge. The results of the activity showed active participation from 12 pregnant women class participants with positive responses to the material presented. Interesting material accompanied by demonstrations of massage and stretching techniques helps increase knowledge of pregnant women. Evaluation before and after the activity showed an increase in knowledge from 5% to 100%, indicating the success of the extension activity.